MAKANAN TABU DI BARITO KUALA KALIMANTAN SELATAN - Dadang Sukandar (Food and Nutrition Society of Indonesia, 2007)
Food taboo in Indonesia is still a problem. As consequences, pregnant mother, lactating mother and children do not eat the taboo foods so that it can reduce their food intake and finally it can decrease their nutritional status. The objectives of this study are 1) to identify taboo foods, 2) to identify reasons of taboo food and 3) to improve basic nutrition knowledge through training on food and nutrition. Study was conducted in Barito Kuala South Kalimantan from December 2005 to November 2006. A sample of size 36 households was drawn randomly from household population of size 180. The households population is household farmer who are beneficiary of Special Program for Food Security, Food and Agriculture Organization. Data were analyzed quantitatively and qualitatively and presented in one way table. Results show that groups which had many food taboo were pregnant woman group and lactating mother group. There are 7 taboo foods for pregnant woman and 11 taboo foods for lactating mother. Some taboo foods for pregnant women are ice, twin banana, young coconut, coconut water, young pineapple and fish. Some taboo foods for lactating mother are egg, fresh fish, fish, sugar, salt, jackfruit, fat food, hot food, etc. After attending training, the knowledge on nutrition and food of the farmers increase significantly, therefore it is hoped that their knowledge can reduce their believe of the food taboo.